Conversion of external percutaneous transhepatic biliary drainage to endoscopic ultrasound-guided hepaticogastrostomy after failed standard internal stenting for malignant biliary obstruction - Paik, Woo Hyun; Lee, Nah Kyum; Nakai, Yousuke; Isayama, Hiroyuki; Oh, Dongwook; Song, Tae Jun; Lee, Sang Soo; Seo, Dong-Wan; Lee, Sung Koo; Kim, Myung-Hwan; Park, Do Hyun (Endoscopy, 2017)
Background and study aim Percutaneous transhepatic biliary drainage (PTBD) is a rescue procedure after a failed endoscopic retrograde cholangiopancreatography. As PTBD causes patient discomfort, conversion of the PTBD to internal biliary stenting (PTBDS) may be required; however, PTBDS is sometimes difficult because of the tight stricture. We evaluated the efficacy and safety of conversion of external PTBD to endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) after failed PTBDS.Patients and methods A total of 16 patients with malignant distal biliary obstruction who underwent conversion of external PTBD to EUS-HGS after failed PTBDS were enrolled from two institutions in Korea and Japan. Data were analyzed retrospectively. Results The technical and clinical success rates were 100 % and 81 %, respectively. Early adverse events developed in two patients: proximal stent migration (n = 1), and cholecystitis (n = 1). Stents were occluded or migrated distally in five patients. The mean duration of stent patency was 402 days.Conclusions Conversion of external PTBD to EUS-HGS may be a good rescue option after failed PTBDS.